2020
DOI: 10.1021/acs.cgd.0c00346
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Complexation of Cellulose/Ionic Liquid at High Cellulose Concentration: Anion Dependence

Abstract: We investigated the state of cellulose that was dissolved in ionic liquid (IL) consisting of 1-methyl-3-propylimdiazolium cation ([C 3 mim] + ) paired with acetate ([OAc] − ), dimethylphospate ([DMP] − ), or chloride (Cl − ) anions using wide-angle X-ray scattering (WAXS), particularly focusing on the high cellulose concentration region (10−80 mol %). The anion species considerably altered the WAXS pattern of the cellulose/IL mixtures. [C 3 mim][OAc] deconstructed cellulose crystal structure up to the 40 mol %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…5−6 nm −1 corresponds to the appearance of a self-assembled structure. 17,22 On the other hand, various sharp Bragg peaks were observed for cellulose I/[C 3 mim]Cl We re-measured these samples, and it was confirmed that the X-ray patterns were almost the same as those previously reported. 17 From Table 1, we can speculate on the preferential chemical structures of cations and anions for the formation of a complex crystal.…”
Section: ■ Materials and Methodssupporting
confidence: 85%
See 4 more Smart Citations
“…5−6 nm −1 corresponds to the appearance of a self-assembled structure. 17,22 On the other hand, various sharp Bragg peaks were observed for cellulose I/[C 3 mim]Cl We re-measured these samples, and it was confirmed that the X-ray patterns were almost the same as those previously reported. 17 From Table 1, we can speculate on the preferential chemical structures of cations and anions for the formation of a complex crystal.…”
Section: ■ Materials and Methodssupporting
confidence: 85%
“…16 In 2020, we discovered cellulose complex crystals with two ILs, 1-methyl-3-propylimidazolium paired with chloride at high cellulose concentrations. 17 This could be the first report of cellulose I/IL as a two-component (i.e., cellulose/IL) system.…”
Section: ■ Introductionmentioning
confidence: 88%
See 3 more Smart Citations